Synthesis of Phosphorodiamidate Morpholino Oligonucleotides (PMOs) Using Staudinger Reduction as a Deblocking Condition and Its Usefulness for Orthogonal Conjugation in Bi- and Trifunctionalized PMOs - Pratihar, Subhamoy; Qasim, Md; Sinha, Surajit (Synlett, 2024)
The synthesis of short phosphorodiamidate morpholino oligonucleotides (PMOs) has been successfully achieved using azidoaryl carbamate protected chlorophosphoramidate monomers. The deprotection step carried out in a neutral medium with triphenylphosphine-based reagents avoids the need for chlorinated solvents. This method uses a meticulously tailored combination of resin support, solvents, deblocking agents, and coupling reagents to ensure efficient synthesis. Additionally, the azidoaryl carbamate protecting group has been adapted as an orthogonal protection, enabling the development of bi- and trifunctionalized PMOs for bioconjugation. These advancements are expected to broaden the potential applications of PMOs in biomedical research.
Keywords: antisense agents; oligonucleotides; protecting groups; conjugation; solid-phase synthesis